(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
Speech culture is one of the most important indicators of a child’s overall development and social adaptation. The preschool period is considered a crucial stage in the formation of speech competence, communication skills, and language behavior. This article examines the pedagogical and psychological conditions necessary for the formation of speech culture in preschool children. Particular attention is paid to the role of the family, preschool educational institutions, educators, and the language environment in developing correct, expressive, and meaningful speech. The study also highlights effective methods and approaches that contribute to the development of speech culture among preschool-aged children.